Citizen-to-citizen connectivity and soft power: The appropriation of subcultures in 'little freshness' across the Taiwan Strait. (November 2019) - Lim, Song Hwee
This article takes as its object of analysis the term 'little freshness' ( xiao qingxin 小清新), which has been coined to describe a variety of cultural products and phenomena, mostly emanating from Taiwan but circulating across the Taiwan Strait. It argues that little freshness is a manifestation of subcultures that have been initiated, appropriated, and consumed by youths in the region. This citizen-to-citizen connectivity reworks Joseph Nye's notion of soft power by shifting the focus away from state agents and by reversing the direction of soft power flows to claim agency at the sites of reception. The article provides two case studies to demonstrate how an imaginary about Taiwan's cleanness, clearness, and freshness has been projected by the media in the People's Republic of China as a form of discursive construction and by Hong Kong citizens of Taiwan as a desirable destination for emigration. Finally, the article situates the little freshness phenomenon in relation to a propensity towards miniaturization in cultural formation in the region, and suggests that this propensity is inflected in a structure of feeling about generational injustice in the face of neoliberal capitalism.